Artists and their books : books and their artists - Reed, Marcia, 1945-; Phillips, Glenn, 1974-; Getty Research Institute (Los Angeles : Getty Research Institute, 2018)
"Presenting eighty editions and unique objects from the Getty Research Institute's special collections, this volume illuminates the current moment of artists' engagement with books, revealing them as an essential medium in contemporary art"--Provided by publisher.
Foreword / Thomas W. Gaehtgens -- The book in general: some new definitions / Marcia Reed -- Rediscovering the radius of the discourses, or David Antin's "Politics of the artist's book" / Glenn Phillips -- Artists and their books/Books and Their Artists.
kunstcatalogus
Keywords: Artists' books; Conceptual art